2018
DOI: 10.1038/s41598-018-25658-4
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive bioinformatics analysis on multiple Gene Expression Omnibus datasets of nonalcoholic fatty liver disease and nonalcoholic steatohepatitis

Abstract: Fatty liver disease is one of the leading causes of chronic damage in western countries. Approximately 25% of adults in the United States have fatty livers in the absence of excessive alcohol consumption, a condition termed nonalcoholic fatty liver disease (NAFLD). Little is known about the prevalence and genetic background of NAFLD or the factors that determine its development. In this study, we used the Gene-Cloud of Biotechnology Information bioinformatics platform to carry out a comprehensive bioinformatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
(37 reference statements)
1
34
0
Order By: Relevance
“…A variety of chemicals, mainly drugs, and diets have been implicated in hepatic steatosis [68]. Moreover, recent studies have indicated that a number of genes play important roles in the development of NAFLD [69]. In the present study, we found that STAT3 was downregulated in NAFLD through bioinformatic analysis and further verified this result by RT-qPCR and western blotting.…”
Section: Discussionsupporting
confidence: 77%
“…A variety of chemicals, mainly drugs, and diets have been implicated in hepatic steatosis [68]. Moreover, recent studies have indicated that a number of genes play important roles in the development of NAFLD [69]. In the present study, we found that STAT3 was downregulated in NAFLD through bioinformatic analysis and further verified this result by RT-qPCR and western blotting.…”
Section: Discussionsupporting
confidence: 77%
“…This network includes NF-κB, whose activation in non-parenchymal cells is generally recognized to promote inflammation, fibrosis and hepatocarcinogenesis [37]. Of significance is also the predicted activation of TP53, a preferential target of DNA-damaging agents, such as tobacco smoke carcinogens [30,50,51], and a key regulator in fatty liver and insulin resistance [52]. TP53 interacts with the NK-kB complex, and crosstalk between the TP53 and NF-kB transcription factors has been shown to play a pivotal role in determining the cellular response to certain stimuli, e.g., DNA damage [53].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in both experimental and clinical settings have shown the mRNA expression of the urea cycle enzymes and the physiological functional capacity to be parallel . This may also be the case in NAFLD where alteration in the hepatic transcriptome has been reported . However, such reports are mainly based on association studies providing limited insight into functional consequences of the altered gene expression and specifically, a possible gene regulatory basis for the deficient urea synthesis capacity has not been studied in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…7 This may also be the case in NAFLD where alteration in the hepatic transcriptome has been reported. [8][9][10] However, such reports are mainly based on association studies providing limited insight into functional consequences of the altered gene expression and specifically, a possible gene regulatory basis for the deficient urea synthesis capacity has not been studied in NAFLD. The issue is important because compromised urea synthesis may lead to such clinical problems as hyperammonaemic cognitive dysfunction, as is already described in NAFLD 11 and favour the progression of disease.…”
Section: Introductionmentioning
confidence: 99%